Case series: Congenital enterovirus infection‐associated haemophagocytic lymphohistiocytosis and subsequent neutropaenia - Justin Penner; James E. Burns; Judith Breuer; Kimberly C. Gilmour; Alasdair Bamford; Anupama Rao (eJHaem, 2024)
Congenital enterovirus infection can be associated with a pro‐inflammatory state triggering haemophagocytic lymphohistiocytosis (HLH). Enteroviruses are also known to cause transient neutropenia in healthy children. Two infants presented with temperature instability, lethargy, thrombocytopaenia, hepatosplenomegaly and evidence of hyperinflammation in the setting of perinatal maternal rash and household contacts with gastrointestinal symptoms. Whilst HLH was successfully treated in both, protracted neutropenia persisted. Immune dysregulation with enterovirus in the neonatal period can provoke the generation of autoantibodies to hematologic cells giving rise to conditions such as autoimmune neutropenia. Sustained neutropaenia, after resolution of secondary infectious forms of HLH, requires investigation for underlying aetiologies.